Stabilising Collective Agreements in Continental Europe - Alexandre de le Court (Oñati Socio-Legal Series)
Most continental European legal systems where normative value is conferred on collective bargaining agreements also include a legal mechanism, known as after-effects, whereby the content of such agreements survives after they expire. After-effects can be regulated by specific legislative provisions. Where such provisions are absent, jurisprudential constructions based on the application of general principles of contract law have been applied instead. This comparative study reveals an important convergence between these models, in terms of both the legal techniques adopted and in the objectives pursued. The study also reveals that states share common concerns around maintaining a certain balance between negotiating parties, whether through consolidating the respective models of collective bargaining or via correcting dysfunctions introduced by emergency measures. Those solutions can be embedded in the international definition of the right to collective bargaining, revealing the importance of a holistic vision on regulations underpinning the European collective bargaining model.